Fabrication Of Iron Oxide Nanoparticles 3-Aminopropyltriethoxysilane Modified Electrode For Cd (Ii) Ions And Pb (Ii) Ions Detection - Arivalakan, Sarasijah (2019)
Heavy metal pollution has become the biggest concern nowadays as it causes various health issues. Most analysis have been carried out in laboratory using Inductively Coupled Plasma Spectrometry and Atomic Absorption Spectrometry that are expensive, requires trained personnel and not suitable for on site analysis. Electrochemical sensors overcome these drawbacks, but the working electrode needs to be modified to enhance its sensitivity and selectivity. In this work, iron oxide nanoparticles (IONPs) was synthesized using co-precipitation method and bismuth particles (BiP) was synthesized by using hydrothermal method. The IONPs was self-assembled on indium tin oxide (ITO) electrode with the aid of 3-aminopropyltriethoxysilane (APTES). The effect of soaking time of APTES/ITO in IONPs (30, 60, 90, 120 and 150 min) was investigated. Electrochemical properties of IONPs/APTES/ITO were studied using cyclic voltammetry (CV) and square wave anodic stripping voltammetry (SWASV) analysis. The 90 min IONPs/APTES/ITO electrode was chosen as the optimum as it showed high conductivity and effective surface area, Ae. The linear range for Cd (II) in individual detection was 1 – 10 ppb with sensitivity of 110.59 μA ppb-1 and limit of detection (LOD) of 2.5 ppb. The sensitivity for Pb (II) was 7.01 μA ppb-1 in the linear range of 50 – 70 ppb with LOD of 2.09 ppb. For simultaneous detection, the linear range for Cd (II) was 30 ppb – 70 ppb with sensitivity of 5.69 μA ppb-1 and LOD of 9.15 ppb. While for Pb (II) the peak was only observed for 80 and 100 ppb. A well-defined peak was produced from interference study, signifying the modified electrode was highly sensitive and selective towards detection of Cd (II). Finally, the IONPs/APTES/ITO electrode was applied for seawater samples, where by Cd (II) was detected with concentration 14.13 ppb and 26.84 ppb for samples from Seagate beach and Pantai Jerejak, respectively. The findings revealed that the IONPs/APTES/ITO electrode can be used as a heavy metal sensor.